Professor coordenador pedagógico: leitura e análise da ação formativa pedagógica registrada no livro de ATPC - Batista, Célia Maria (2021)
This research is part of the set of investigations related to the line of research called School Institute: Organization, pedagogical practices and educator training in the Postgraduate Studies Program in Education, History, Politics, Society at PUC-SP and aims to analyze expression of the formative actions of work collective meetings, using like qualitative approach the technique of document applied to the record books of Class of Collective Pedagogical Work (CCPW) of five state public schools of different years and segments, between the years of 2014 to 2018. This space is intended to provide educational orientation for the cultural and pedagogical updating and improvement of teachers with a focus on teaching quality. My hypothesis is based on the assumption of which collaborations the Class of Collective Pedagogical Work (CCPW) promotes in the cultural and pedagogical improvement of the teacher, in the process of preparing classes, teaching material, evaluating their students and in the process of integration school-community. As this is an empirical study and for better verification in the reading of CCPW book, this research has secondary objectives that show what happens in the CCPW: what is the content of the discussions that are done; which formative action takes place at that moment; what aspects of school pedagogical work does it reach; how is performance of Coordinating Teacher (CT) works and what the school's problems are debated in this training space. After analyzing the CCPW books, one concludes that there is no training space that aims to reach students by potentializing the classes. We observed that the CCPW's prioritize trivial themes over important themes such as learning goals, methodological conception of teaching, assessment and curriculum. It is understood that, what should be moment's continuing training in service provided for in the weekly working hours of teachers under the responsibility of the Coordinating Teacher, has been used for meetings that do not add to their respective practices, that is, they do not demonstrate essentiality, observed in situations such as the lack of pragmatism in the construction of the agenda and the absence of record of minutes